The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1016/j.infbeh.2006.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Moderate versus light pressure massage therapy leads to greater weight gain in preterm infants

Abstract: Sixty-eight preterm infants (M GA=3Owks.) were randomly assigned to a moderate or to a light pressure massage therapy group to receive 15 massages 3 times per day for 5 days. Behavior state, stress behaviors and heart rate were recorded for 15 minutes before and during the first 15-minute therapy session. Weight gain was recorded over the 5 day therapy period. The moderate versus light pressure massage group gained significantly more weight per day. During the behavior observations the moderate versus light pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
2
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(124 citation statements)
references
References 11 publications
2
110
2
10
Order By: Relevance
“…Massage therapy in 10 out of the 12 articles consists of a 15 min massage session, which includes tactile stimulation with moderate pressure on the limbs and trunk and kinesthetic stimulation on the four limbs [3,6,[11][12][13][14][15][17][18][19]. The other two massage methods are a 20 min touch procedure adopted by Livingston et al [8] and acupressure and meridian massage adopted by Chen et al [16].…”
Section: Massage Methods and Delivery Modesmentioning
confidence: 99%
See 4 more Smart Citations
“…Massage therapy in 10 out of the 12 articles consists of a 15 min massage session, which includes tactile stimulation with moderate pressure on the limbs and trunk and kinesthetic stimulation on the four limbs [3,6,[11][12][13][14][15][17][18][19]. The other two massage methods are a 20 min touch procedure adopted by Livingston et al [8] and acupressure and meridian massage adopted by Chen et al [16].…”
Section: Massage Methods and Delivery Modesmentioning
confidence: 99%
“…All trials wherein the massage was provided by qualified therapists showed a positive result; that is, the massage group gained more weight than the control and/or sham group [3,6,[11][12][13][14].…”
Section: Massage Methods and Delivery Modesmentioning
confidence: 99%
See 3 more Smart Citations